Improving Fine Motor Skills through the Use of Plasticine Media - Yanti, Desri; Salumiza (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve fine motor skills through the use of plasticine media among Group A children at TK Kharisma. The research method used is Classroom Action Research (CAR), which was conducted in two cycles. The research subjects consisted of 23 children, including 13 boys and 10 girls. The data collection techniques used were observation, interviews, and documentation. Data analysis was carried out using descriptive qualitative and descriptive quantitative methods. The results of the study showed an improvement in children’s fine motor skills through the use of plasticine media. The results of the pre-action observation reached 34%, Cycle I achieved 61%, and Cycle II increased to 82%. This indicates that the research success criteria were met, showing a significant improvement of 82%. Based on these findings, it can be concluded that the use of plasticine media effectively enhances the fine motor skills of children aged 4–5 years.